Ecotonal gradients shape biodiversity of multiple estuarine taxa - Rebecca Oester; Benjamin Branoff; Johanna Biederbick; Luise Grüterich; Raphael Koll; Fay Lexmond; Nele Martens; Julian Mittmann-Goesele; Friederike Neiske; Widhi Putri; Sina Remmers; Diana Richter; et al. (Estuarine, Coastal and Shelf Science, 2026)

Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Tropical root responses to global changes: A synthesis - Daniela Yaffar; Laynara F. Lugli; Michelle Y. Wong; Richard J. Norby; Shalom D. Addo‐Danso; Marie Arnaud; Amanda L. Cordeiro; Lee H. Dietterich; Milton H. Diaz‐Toribio; Ming Y. Lee; Om Prakash Ghimire; Chris M. Smith‐Martin; et al. (Global Change Biology, 2024)
Tropical ecosystems face escalating global change. These shifts can disrupt tropical forests' carbon (C) balance and impact root dynamics. Since roots perform essential functions such as resource acquisition and tissue protection, root responses can inform about the strategies and vulnerabilities of ecosystems facing present and future global changes. However, root trait dynamics are poorly understood, especially in tropical ecosystems. We analyzed existing research on tropical root responses to key global change drivers: warming, drought, flooding, cyclones, nitrogen (N) deposition, elevated (e) CO 2 , and fires. Based on tree species‐ and community‐level literature, we obtained 266 root trait observations from 93 studies across 24 tropical countries. We found differences in the proportion of root responsiveness to global change among different global change drivers but not among root categories. In particular, we observed that tropical root systems responded to warming and eCO 2 by increasing root biomass in species‐scale studies. Drought increased the root: shoot ratio with no change in root biomass, indicating a decline in aboveground biomass. Despite N deposition being the most studied global change driver, it had some of the most variable effects on root characteristics, with few predictable responses. Episodic disturbances such as cyclones, fires, and flooding consistently resulted in a change in root trait expressions, with cyclones and fires increasing root production, potentially due to shifts in plant community and nutrient inputs, while flooding changed plant regulatory metabolisms due to low oxygen conditions. The data available to date clearly show that tropical forest root characteristics and dynamics are responding to global change, although in ways that are not always predictable. This synthesis indicates the need for replicated studies across root characteristics at species and community scales under different global change factors.

Temperature effects on root exudation in mature beech (Fagus sylvatica L.) forests along an elevational gradient - Christoph Leuschner; Timo Tückmantel; Ina C. Meier (Plant and Soil, 2022)
Aims Root exudation may have a large impact on soil biological activity and nutrient cycling. Recent advances in in situ -measurement techniques have enabled deeper insights into the impact of tree root exudation on rhizosphere processes, but the abiotic and biotic controls of exudation rate remain poorly understood. We explored the temperature dependence of root exudation in mature beech ( Fagus sylvatica L.) trees. Methods We measured fine root exudation in seven beech forests along an elevational gradient (310–800 m a.s.l.) and related carbon (C)-flux rates to mean daily temperature, actual precipitation, mean summer temperature (MST) and precipitation (MAP), soil moisture (SWC), and stand structure. Results Average mass-specific exudation (averaged over all sampling dates) ranged from 12.2 µg C g −1 h −1 to 21.6 µg C g −1 h −1 with lowest rates measured at highest elevations and peak rates at mid-elevation (490 m). Regression analyses showed a highly significant positive effect of site-specific daily air and soil temperature on exudation rates ( p < 0.01) with an average increase by 2 µg C g −1 h −1 per 1 °C-temperature increase, while the relation to mean summer or annual temperature and mean temperature of the measuring year was less tight. Exudation decreased with increases in mean annual precipitation and soil moisture, but increased with increasing stem density. Conclusions The root exudation rate of beech trees roughly triples between 10 °C and 20 °C mean daily temperature, evidencing a large temperature influence on root-borne C flux to the soil.

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

Roots and fungi accelerate carbon and nitrogen cycling in forests exposed to elevated CO 2 - Richard P. Phillips; Ina C. Meier; Emily S. Bernhardt; A. Stuart Grandy; Kyle Wickings; Adrien C. Finzi (Ecology Letters, 2012)
A common finding in multiple CO 2 enrichment experiments in forests is the lack of soil carbon ( C ) accumulation owing to microbial priming of ‘old’ soil organic matter ( SOM ). However, soil C losses may also result from the accelerated turnover of ‘young’ microbial tissues that are rich in nitrogen ( N ) relative to bulk SOM . We measured root‐induced changes in soil C dynamics in a pine forest exposed to elevated CO 2 and N enrichment by combining stable isotope analyses, molecular characterisations of SOM and microbial assays. We find strong evidence that the accelerated turnover of root‐derived C under elevated CO 2 is sufficient in magnitude to offset increased belowground inputs. In addition, the C losses were associated with accelerated N cycling, suggesting that trees exposed to elevated CO 2 not only enhance N availability by stimulating microbial decomposition of SOM via priming but also increase the rate at which N cycles through microbial pools.

Variation of soil and biomass carbon pools in beech forests across a precipitation gradient - INA C. MEIER; CHRISTOPH LEUSCHNER (Global Change Biology, 2010)
Temperate forests have recently been identified as being continuing sinks for carbon even in their mature and senescent stages. However, modeling exercises indicate that a warmer and drier climate as predicted for parts of Central Europe may substantially alter the source/sink function of these economically important ecosystems. In a transect study with 14 mature European beech ( Fagus sylvatica L.) forests growing on uniform geological substrate, we analyzed the influence of a large reduction of annual precipitation (970–520 mm yr −1 ) on the carbon stocks in fast and slow pools, independent of the well‐known aging effect. We investigated the C storage in the organic L, F, H layers, the mineral soil to 100 cm, and in the biomass (stem, leaves, fine roots), and analyzed the dependence of these pools on precipitation. Soil organic carbon decreased by about 25% from stands with > 900 mm yr −1 to those with −1 ; while the carbon storage in beech stems slightly increased. Reduced precipitation affected the biomass C pool in particular in the fine root fraction but much less in the leaf biomass and stem fractions. Fine root turnover increased with a precipitation reduction, even though stand fine root biomass and SOC in the organic L, F, and H layers decreased. According to regression analyses, the C storage in the organic layers was mainly controlled by the size of the fine root C pool suggesting an important role of fine root turnover for the C transfer from tree biomass to the SOC pool. We conclude that the long‐term consequence of a substantial precipitation decrease would be a reduction of the mineral soil and organic layer SOC pools, mainly due to higher decomposition rates. This could turn temperate beech forests into significant carbon sources instead of sinks under global warming.

Belowground drought response of European beech: fine root biomass and carbon partitioning in 14 mature stands across a precipitation gradient - INA C. MEIER; CHRISTOPH LEUSCHNER (Global Change Biology, 2008)
How tree root systems will respond to increased drought stress, as predicted for parts of Central Europe, is not well understood. According to the optimal partitioning theory, plants should enhance root growth relative to aboveground growth in order to reduce water limitations. We tested this prediction in a transect study with 14 mature forest stands of European beech ( Fagus sylvatica L.) by analysing the response of the fine root system to a large decrease in annual precipitation (970–520 mm yr −1 ). In 3 years with contrasting precipitation regimes, we investigated leaf area and leaf biomass, fine root biomass and necromass (organic layer and mineral soil to 40 cm) and fine root productivity (ingrowth core approach), and analysed the dependence on precipitation, temperature, soil nutrient availability and stand structure. In contrast to the optimal partitioning theory, fine root biomass decreased by about a third from stands with >950 mm yr −1 to those with −1 , while leaf biomass remained constant, resulting in a significant decrease, and not an increase, in the fine root/leaf biomass ratio towards drier sites. Average fine root diameter decreased towards the drier stands, thereby partly compensating for the loss in root biomass and surface area. Both δ 13 C‐signature of fine root mass and the ingrowth core data indicated a higher fine root turnover in the drier stands. Principal components analyses (PCA) and regression analyses revealed a positive influence of precipitation on the profile total of fine root biomass in the 14 stands and a negative one of temperature and plant‐available soil phosphorus. We hypothesize that summer droughts lead to increased fine root mortality, thereby reducing root biomass, but they also stimulate compensatory fine root production in the drier stands. We conclude that the optimal partitioning theory fails to explain the observed decrease in the fine root/leaf biomass ratio, but is supported by the data if carbon allocation to roots is considered, which would account for enhanced root turnover in drier environments.

Leaf Size and Leaf Area Index in Fagus sylvatica Forests: Competing Effects of Precipitation, Temperature, and Nitrogen Availability - Ina C. Meier; Christoph Leuschner (Ecosystems, 2008)